Information packaging in Functional Discourse Grammar - Smit, Niels (ALFA: Revista de Linguística, 2009)
The paper addresses the modelling of information packaging in Functional Discourse Grammar (FDG), in particular the treatment of Topic, Comment and Focus. Current FDG has inherited the traditional Functional Grammar (FG) representation of these categories as functions, which attach to Subacts of evocation. However, arguments of a formal, notional and descriptive nature can be advanced against pragmatic function assignment and in favour of an alternative analysis in which informational and evocational structures are dissociated so as to command their own primitives. In the context of a model of discourse knowledge organisation in which communicated contents are associated with packaging instructions that tell the Addressee how to treat the evoked knowledge, it is argued that focality can be modelled by means of a Focus operator that can attach to various constituents at the Interpersonal Level. Topicality, on the other hand, concerns binomial and monomial modes of presenting communicated contents. This can be rendered by means of the dedicated informational units Topic (Top) and Comment (Cm), that interact in frames.